2015
DOI: 10.1128/mbio.01005-15
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunization with Newcastle Disease Virus Vector Coexpressing HIV-1 Env and Gag Proteins Elicits Potent Serum, Mucosal, and Cellular Immune Responses That Protect against Vaccinia Virus Env and Gag Challenges

Abstract: Newcastle disease virus (NDV) avirulent strain LaSota was used to coexpress gp160 Env and p55 Gag from a single vector to enhance both Env-specific and Gag-specific immune responses. The optimal transcription position for both Env and Gag genes in the NDV genome was determined by generating recombinant NDV (rNDV)-Env-Gag (gp160 located between the P and M genes and Gag between the HN and L genes), rNDV-Gag-Env (Gag located between the P and M genes and gp160 between the HN and L genes), rNDV-Env/Gag (gp160 fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…To evaluate the efficacy of antipoliovirus vaccination with the NDV-polio construct, we performed intranasal immunization of guinea pigs. Previous research indicates that the immune response of guinea pigs to NDV vector-based vaccines resembles that observed in primate models (31,38,39). Four animals in each group were immunized with either NDV-polio or the NDV vector without poliovirus inserts.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the efficacy of antipoliovirus vaccination with the NDV-polio construct, we performed intranasal immunization of guinea pigs. Previous research indicates that the immune response of guinea pigs to NDV vector-based vaccines resembles that observed in primate models (31,38,39). Four animals in each group were immunized with either NDV-polio or the NDV vector without poliovirus inserts.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the titer of Env-specific IgG in serum was sustained at the peak response level for at least 160 days, there was a marginal decline in the mucosal IgG titer in vaginal washes. Recently, we demonstrated that immunization of guinea pigs with rNDV expressing gp160 without any protein boost elicited long-lasting systemic and mucosal immune responses to HIV (14). These findings indicate that the long-lasting antibody response may be strongly influenced by the use of rNDV vector as a prime.…”
Section: Figmentioning
confidence: 97%
“…There is no preexisting immunity to NDV in humans. NDV infects via the intranasal and oral routes and induces both mucosal and systemic immune responses (9)(10)(11)(12)(13)(14)(15)(16)(17). Previously, we demonstrated the potential of NDV as a vaccine vector for HIV-1 (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…An exogene can be placed at the gene junction between any two genes of the virus, yet the 3 rd position has been found to be the most optimal for NDV vector [149,182,185,186] with the 1 st and the 2 nd ones being the least optimal [148,149]. NDV has been used for vectoring the antigens of RSV [185], AMPV [187][188][189], HIV [149,190,191], HPIV3 [182], influenza A virus [192], SARS-coronavirus [186], Nipah virus [193], and Ebola virus [194]. Examples of NDV vectoring pneumoviral antigens are reported in Table 4.…”
Section: Newcastle Disease Virusmentioning
confidence: 99%